1996
DOI: 10.3109/10826089609072284
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Retention in Women's Residential Chemical Dependency Treatment: The Effect of Admission with Children

Abstract: In the United States there has been an increased interest in the development of treatment programs that admit chemically dependent women with their children. The Salvation Army Family Treatment Services in Honolulu, Hawaii has had a long history of admitting women both with and without their children to long-term residential treatment. This has provided an opportunity to study the differences in treatment retention between these two groups. Subjects were 130 females who participated in treatment between 1988 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…The results showed that the women who retained their children remained in residential treatment significantly longer than the other women. This finding was confirmed in a quasi-experimental study: women who participated in residential treatment with children had higher retention rates than women without children in treatment (Szuster et al, 1996).…”
Section: Program-related Characteristics Associated With Treatment Rementioning
confidence: 57%
See 2 more Smart Citations
“…The results showed that the women who retained their children remained in residential treatment significantly longer than the other women. This finding was confirmed in a quasi-experimental study: women who participated in residential treatment with children had higher retention rates than women without children in treatment (Szuster et al, 1996).…”
Section: Program-related Characteristics Associated With Treatment Rementioning
confidence: 57%
“…This project found that the women were significantly more likely to complete the women-focused intensive day program than those who attended a residential program for women and their children or a traditional residential program (Roberts and Nishimoto, 1996). Within residential programs, however, policies allowing children to accompany their mothers in treatment have been demonstrated to have a positive impact on treatment retention (Hughes et al, 1995;Szuster et al, 1996). A randomized trial of female cocaine-abusing patients assigned women to the experimental condition, in which one or two of the children joined the woman in residential treatment, or the control condition of placing the children with a caregiver outside the therapeutic community (Hughes et al, 1995).…”
Section: Program-related Characteristics Associated With Treatment Rementioning
confidence: 99%
See 1 more Smart Citation
“…The study used a nondirectional hypothesis since this was an exploratory study. While most studies indicate that women who have their children with them in treatment were likely to complete treatment (Hughes, Coletti, Neri, Urmann, 1995;Knight, Logan, & Simpson, 2001;Nishimoto & Roberts, 2001;Stahl, Sicillian, & Anthony, 1995;Szuster, Rich, Chung, & Bisconer;Strantz, & Welch, 1995), at least one study suggests that women who had custody of their children and who had significant child care responsibilities were less likely to complete treatment (Knight, Logan, & Simpson, 1999). Further, much of the relevant TANF research is descriptive, and there is little research that assesses the impact of receiving TANF cash benefits on women's drug treatment outcomes (Gutman, Ketterling & McLellan 2003;Keesee & Williams, 1997;Montoya, Atkinson & Struse, 2001).…”
Section: Textmentioning
confidence: 99%
“…Women who have their infant/children during treatment tend to remain in treatment longer and have improved outcomes (Ashley, Marsden & Brady, 2003;Hughes et al, 1995;Szuster, Rich, Chung & Bisconer 1996;Wobie, Eyler, Conlon, Clarke & Behnke, 1997). Providing parenting skills improves the ID/SA mothers' parenting attitude and knowledge, self-esteem that affects maternal-child interaction and yield healthier infants/children (Camp & Finkelstein, 1997;Christensen, Brayden, Dietrich, McLaughlin, Sherrod & Altimer, 1994).…”
Section: Residential Rehabilitation Programmentioning
confidence: 99%